2021
DOI: 10.3390/ma15010036
|View full text |Cite
|
Sign up to set email alerts
|

Deformations in Cement Pastes during Capillary Imbibition and Their Relation to Water and Isopropanol as Imbibing Liquids

Abstract: The traditional approach for evaluating capillary imbibition, which describes the phenomena as a linear relationship between mass gain and the square root of time, considers a rigid pore structure. The common deviation from the linearity when using the square-root law (manifested in a downward curvature, i.e., slower water ingress) can be explained by considering a changing pore structure during the process caused by the swelling of calcium silicate hydrate (C-S-H) during water ingress. Analysing how the combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
(111 reference statements)
0
1
0
Order By: Relevance
“…However, techniques are now advancing due to recognition of the significant non-linearity that is observed during the water absorption process in cementitious materials. While measurements of sample deformation have recently suggested that non-linear absorption begins very early on in the absorption process, 62 this becomes especially prevalent in the absorption data beyond a duration of between 6 and 24 hours, and the numerous testing standards deal with this in various ways. For example, the ASTM C1585 standard 8 divides absorption into two periods, the first up to 6 hours and the second beyond 24 hours, while EN 13057:2002 neglects one or the other portion of the curve depending on whether or not full saturation of the sample is reached within 24 hours.…”
Section: Resultsmentioning
confidence: 99%
“…However, techniques are now advancing due to recognition of the significant non-linearity that is observed during the water absorption process in cementitious materials. While measurements of sample deformation have recently suggested that non-linear absorption begins very early on in the absorption process, 62 this becomes especially prevalent in the absorption data beyond a duration of between 6 and 24 hours, and the numerous testing standards deal with this in various ways. For example, the ASTM C1585 standard 8 divides absorption into two periods, the first up to 6 hours and the second beyond 24 hours, while EN 13057:2002 neglects one or the other portion of the curve depending on whether or not full saturation of the sample is reached within 24 hours.…”
Section: Resultsmentioning
confidence: 99%